The Antioxidant Properties And Anticancer Effect Of Medjool Dates (phoenix Dactylifera L.) On Human Breast Adenocarcinoma (MCF-7) Cells: In Vitro Study - Ismail Rozila; Najwa Mawaddah Abdul Manap; Liana Nazurah Ghazali; Nurkhalida Kamal; Waheedah Abdul Hakeem; Shiplu Roy Chowdhury; Shamima Abdul Rahman; Nur Fariha Mohd Manzor (Frontiers Media S.A, 2024)
Indexed by ERA